The genealogical construction of the Kyrgyz Republic kinship, state and "tribalism" - Gullette, David; ebrary, Inc. (Folkestone : Global Oriental, 2010)
In this important new study on the peoples of the Kyrgyz Republic (Kyrgyzstan), David Gullette exposes significant misconceptions that have hitherto shaped Western understanding about the role of kinship in Kyrgyz society and offers new insights into notions of relatedness.
In a paradigmatic shift, Gullette analyses how people's exploration of genealogy serves to establish relatedness between groups and individuals through shared memories of ancestors, but not to define social structure. His examination of personal accounts of honouring ancestors and fulfilling family obligations reveals how moral values are transmitted through genealogies and how social relations are maintained to receive help through family networks.
History, which shapes memories, became the vehicle for a national campaign through which former President Askar Akaev adapted these relations to create an ethnic and state ideology of unity. By introducing and exploiting national celebrations, the former president not only advanced the ideals of the republic, but also introduced elements of self-discipline. Gullette utilizes genealogy to explore the contexts in which these celebrations were conducted and the value placed on them for the Akaev regime's longevity.
Students of anthropology, international relations and political science, as well as those interested in regional studies, will welcome the solid analytical and theoretical structure of this book. --Book Jacket.
Includes bibliographical references (p.[195]-214) and index.
Electronic reproduction.
Keywords: Kyrgyz -- Ethnic identity -- History; Kinship -- Kyrgyzstan; Nationalism -- Kyrgyzstan; Kyrgyzstan -- Civilization; Electronic books